PO57 Untargeted Metabolomic Analysis by LC-MS for the differentiation of arazá (Eugenia stipitata) subspecies. - Galeano García, Paula Liliana; Ibañez, Elena; Cifuentes, Alejandro; Valdes, Alberto; Mendiola, Jose (Revista Productos Naturales, 2025)
Eugenia stipitata is a perennial tree belonging to the Myrtaceae family that is native to the Amazon rainforest. It was characterized by McVaugh in 1956 based on samples collected in Peru, Brazil, Bolivia, and Colombia.